Study of all solid-state rechargeable fluoride ion batteries based on thin-film electrolyte - Anji Munnangi (Journal of Solid State Electrochemistry, 2017)
In this work, a solid-state fluoride ion battery based on a thin-film electrolyte with 10 μm thickness was built and tested. The electrochemical performance was examined using Bi or Cu metals as the active cathode materials and MgF2 as the active anode material, respectively. X-ray diffraction and X-ray photoelectron spectroscopy data showed that the charge transfer ions between the cathode and anode were fluoride ions. Initial discharge capacities of 66 and 76 mAh g−1 were obtained at 160 °C when Bi and Cu were used as cathodes, respectively. Furthermore, this type of fluoride ion battery was rechargeable, but the capacity faded during the subsequent cycles, similar to the bulk-type systems.